BUDAYA ORGANISASI: ANALISIS DESKRIPTIF FAKTOR INVOLVEMENT, CONSISTENCY, ADAPTABILITY DAN MISSION - Riani, Dini (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
A good and strong culture will encourage employees and leaders to carry out activities in accordance with the organization's strategy or in other words a conducive and strong culture will encourage the organization to achieve its goals. This research uses descriptive analysis by looking at each dimension of the organizational culture variable. The analysis is carried out on each indicator item and concluded based on each dimension. Data collection involved various employees who were members of the FKIP Unpas alumni association who worked in service companies. The research results provide an overall picture of organizational culture. with the average value of the organizational culture variable consisting of the dimensions of involvement, consistency, adaptability and mission interpreted in the Strong criteria. Of these dimensions, the Consistency dimension provides the strongest contribution, while the Involvement dimension provides the weakest contribution. Thus, an organization that has a system of meaning that is shared by its members, has basic assumptions that explain the goals of the organization, it can be said that the organization has an organizational culture.